Bacterial risks and determination of critical control points at the industrial production of chicken edible egg - Demianenko, Denys (ScienceRise: Biological Science, 2023)
The aim: study the bacterial risks and to determine the control critical points at the industrial production of chicken edible egg. Materials and methods. The first stage of our research was to study the degree of risk of contamination by opportunistic and pathogenic microflora at all stages of production of chicken edible eggs according to ISO 22000:2007. In order to achieve the goal, bacteriological research was conducted on pathological material from day-old chickens and adult birds, the content of marketable eggs from birds of different age groups; as well as washed from the equipment of poultry farms, the repair young poultry department, the industrial herd department, egg sorting and certification workshops, from the surface of the egg, from the working surfaces of special vehicles. Bacterial contamination of air, droppings, bedding, complete feed was studied. Bacteriological studies were carried out according to generally accepted schemes, using accumulative, selective and differential diagnostic media (heptadecyl sulfate agar, endo, xylose-lysine agar, differentiated agar with diamond green, Muller-Hinton). The sampling was carried out using universal sterile applicators "Voles". The next stage was to analyze the results of bacteriological studies and determine the basic list of criteria for creating critical control points (CCPs) for the further development of a risk management scheme for the bacterial biosafety of edible eggs according to HACCP principles. Results. Isolation of S. aureus from the heart and lungs, E. coli, P. aeruginosa, Enterobacter spp, Enterococcus spp - from the intestines of day-old chickens and litter - indicate violations of veterinary and sanitary standards in the hatchery and the low quality of disinfection before the placement of day-old young birds, as well as non-observance of veterinary and sanitary norms for the transportation regime of day-old young birds. Isolation of E. coli, Enterobacter spp, Klebsiella spp.Str. zymogenes from compound feed, and E. coli, Enterobacter spp, Shigella spp. in washings from the equipment of the feed mill is evidence of insufficient veterinary and sanitary control of incoming raw materials, compound feed, as well as poorly carried out disinfection of equipment and specialized vehicles.When examining objects from the production line, E. coli, Enterobacter spp., P. aeruginosa, and S. epiderrmidis were most often isolated. From the pathological material during the bacteriological examination, microflora of the genus E. coli, Streptococcus spp., S. aureus (most often pathogenic serotypes) prevailed. As a result of the analysis of the conducted studies, we determined a basic list of criteria for creating a CCP and developing a risk management scheme for the bacterial biosafety of edible eggs according to the principles of HACCP. Conclusions. As a result of the bacteriological monitoring of objects of the technological cycle of chicken edible egg production, we established a list of bacteriological risks at all stages of production. As a result of the conducted research, it was determined, that the spectrum of bacterial contamination was mainly represented by opportunistic microflora. In the majority, the following types of microorganisms were detected: E. coli, P. aeruginosa, Enterobacter spp, Enterococcus spp. But C. jejuni, Streptococcus spp., S. aureus. Salmonella spp, which are the most dangerous for the consumer and poultry, were not isolated. We studied the bacterial risks at all the main stages of the industrial production of chicken edible eggs and identified the main critical control points of production according to the principles of the HACCP system